(untitled) (Asian Journal of Pharmaceutics (AJP), 2015)
The objective of this study was to develop modified release dosage forms of tramadol hydrochloride using wax matrixÂ system by melt granulation method.The effect of various waxes, concentration of waxes, effect of excipients on the releaseÂ profile of drug from wax matrix system was studied. Release retardant effect was observed in the order of hydrogenatedÂ vegetable oil (HVO) > compritol >precirol. This may be due to more lipophilicity imparted by HVO than any other waxyÂ substances. It was also observed that as ratio of drug: Wax was increased, it sustained release of drug for more time.This mayÂ be due to proper embedment/entrapment of drug in sufficient wax matrix system. In case of excipients, release retardantÂ effect was found in order of dicalcium phosphate (DCP) > microcrystalline cellulose (MCC) > lactose. DCP is insoluble which helps in release retardation of drug. MCC is hydrophilic swellable polymer which showed release of drug by swelling. Lactose is soluble excipient which get dissolved and formed channels for entry of dissolution medium and release of drug occurred by erosion mechanism. Wax matrix tablets were found to be stable. Key words: Melt granulation, tramadol hydrochloride, wax matrix tablet